2007
DOI: 10.1111/j.1524-475x.2007.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of wound drainage fluids as a source of soluble factors associated with wound healing: comparison with platelet‐rich plasma and potential use in cell culture

Abstract: Wound fluids, human serum from platelet-poor and platelet-rich plasma (SPPP and SPRP), contain various soluble factors involved in cell growth and proliferation. Levels of cytokines, chemokines, and matrix metalloproteinases (MMPs) in drainage fluids (DFs) harvested from subcutaneous wounds, punctured fluids (PF) from seroma, and SPPP were measured. SPPP and SPRP from four healthy volunteers were also subjected to the analysis. Biochemical profiles of DF reflected the sequential stages of wound healing. Early-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
77
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 41 publications
0
77
1
Order By: Relevance
“…17,22,23 Recently, it was also demonstrated that EGF is released from apoptotic ECs and activates antiapoptotic response in mesenchymal stem cells. 24 AIC does not contain either VEGF or hepatocyte growth factor (HGF), which are considered to be major proangiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,22,23 Recently, it was also demonstrated that EGF is released from apoptotic ECs and activates antiapoptotic response in mesenchymal stem cells. 24 AIC does not contain either VEGF or hepatocyte growth factor (HGF), which are considered to be major proangiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The final concentration of AIC was 2.5 ng/mL PDGF, 1 ng/mL TGF-␤, 10 ng/mL bFGF, and 2 ng/mL EGF (all from Wako Pure Chemicals, Osaka, Japan) mixed in an appropriate solution (EBM containing 0% or 2% FBS in vitro or PBS in vivo); the proportion of the four factors was determined in a previous study, 17 and the concentrations were determined based on a preliminary experiment. hASCs or HUVECs were plated in a six-well plate at 2 ϫ 10 4 cells per well in EBM containing 2% FBS with AIC or without AIC (control).…”
Section: Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The alpha granules of platelets contain a variety of growth factors, cytokines and chemokines. [24][25][26] In particular PDGF, IGF, and chemokines may account for the stimulatory effect of PRP on subchondral progenitor cell migration. Among other growth factors, PDGFbb, IGF-I, and IGF-II have been shown to recruit human mesenchymal progenitor cells derived from bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MMP-1 expression is induced in response to exogenous signals, such as various cytokines or growth factors, cell-matrix interactions, and cell-cell interactions [14,15]. Indeed, a recent study has shown that MMP-1 expression is induced during the process of wound healing [25]. Therefore, it may be possible that physical skin injury induces the local expression of (24) 18 (49) Normal ( …”
Section: Discussionmentioning
confidence: 99%